PENERAPAN PENDIDIKAN KARAKTER DI SEKOLAH - Sri Mardiyah (Edification Journal : Pendidikan Agama Islam, 2019)
Character or attitude or character is an inseparable component of a teaching and learning process and education. Character is formed from home, from the socialization of parents and the environment and can be well implanted in school. The application of character education in schools can be done through daily activities in schools both in teaching and learning activities, practicum and rest hours, both in routine activities, school conditioning and other routine activities. In addition, the internalization of character education can be done through extra-curricular activities in the form of student activity workshops, development of talent and interest groups, life skills education, competitions and competitions and school environment development. In addition to the above, internalization of character education is important to be socialized to parents through collaboration between school and family or parents.